Vow of justice eaudiobook - Eason, Lynette (Blue Justice, 2019)
FBI Special Agent Lincoln St. John is living his own personal nightmare. When the woman he loves, Allison Radcliffe, is killed, he devotes his life to tracking down the killers and making them pay for their crimes. He expected it to be a challenge. What he never expected was to find Allison very much alive shortly after her "murder." As his anger and hurt mix with relief, Linc isn't sure how he's supposed to feel. One thing he does know for sure: he and Allison will have to work together to stop a killer before she dies a second time—this time for good. Bestselling and award-winning author Lynette Eason closes out her Blue Justice series with a story that will have you staying up all night to get to the stunning conclusion.